2016
DOI: 10.1016/j.watres.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment of abandoned mine drainage and Marcellus Shale flowback water for use in hydraulic fracturing

Abstract: Flowback water generated during shale gas extraction in Pennsylvania is mostly reused for hydraulic fracturing operation. Abandoned mine drainage (AMD), one of the most widespread threats to water quality in Pennsylvania, can potentially serve as a make-up water source to enable flowback water reuse. This study demonstrated co-treatment of flowback water and AMD produced in northeastern Pennsylvania in a pilot-scale system consisting of rapid mix reactor, flocculation tank and sedimentation tank. Sulfate conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…54 Many studies suggest that TENORM waste from the oil and gas industry generates radiation exposure levels more than EPA's established limits for Ra-226 and Ra-228. 5,12,21,24,34,[37][38][39][40][41] These studies suggest that more careful monitoring of NORM and TENORM wastes may be necessary to protect the public and workers. For example, a recent study in Wyoming found that fracking waste had a negative impact on water supplies, with evidence of organic compounds and increased salinity in groundwater supplies, the latter of which is a conducive environment for radium migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Many studies suggest that TENORM waste from the oil and gas industry generates radiation exposure levels more than EPA's established limits for Ra-226 and Ra-228. 5,12,21,24,34,[37][38][39][40][41] These studies suggest that more careful monitoring of NORM and TENORM wastes may be necessary to protect the public and workers. For example, a recent study in Wyoming found that fracking waste had a negative impact on water supplies, with evidence of organic compounds and increased salinity in groundwater supplies, the latter of which is a conducive environment for radium migration.…”
Section: Discussionmentioning
confidence: 99%
“…37 These radionuclides may contaminate well sites, be present in the surface runoff, with the possibility of spreading into municipal water systems. 38 TENORM also includes scales, sludges, and contaminated equipment. Studies that evaluated TENORM waste generated during drilling found Ra-226 (speculated to be the most hazardous to human health) to be well over EPA's established limits for radium.…”
Section: Radiological Risks From Tenorm Waste In Oil and Gas Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Active AMD treatment utilizes addition of alkaline chemicals or oxidants (Goodwill et al, 2019;Singer and Stumm, 1970) and ongoing energy inputs for pumping, mixing, and/or aeration (Coulton et al, 2003;Mitsch and Wise, 1998). There are several additional options for co-treating AMD with other waste streams, including the use of organic solid waste substrates or flowback water produced from hydraulic fracturing (Chang et al, 2000;He et al, 2016). Although these co-treatment options improve water quality, disadvantages exist including the need for construction of treatment infrastructure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…limestone dissolution, engineered wetlands) and active (e.g., chemical addition) treatment approaches (Hedin et al 1994;Johnson and Hallberg 2005;Watzlaf et al 2004). However, additional approaches can include co-treating AMD with other wastes such as organic solid waste substrates, agricultural slurry, fracking flowback water, or municipal wastewater (MWW) (Chang et al 2000;He et al 2016;Hughes and Gray 2013a;McDevitt et al 2020). Benefits of co-treating AMD with other wastewaters includes providing low cost AMD abatement, improving effluent quality from treatment systems, and mitigating AMD impacts on receiving bodies.…”
Section: Introductionmentioning
confidence: 99%